Perancangan Buku Ilustrasi Digital Untuk Masyarakat Umur 20-35 Tahun Tentang Kekerasan Terhadap Anak Usia Dini Dan Pengaruhnya Pada Perkembangan Psikologis - Toby Fajar Febriyanto; Sayid Mataram (Wimba : Jurnal Komunikasi Visual, 2023)
The early childhood phase, spanning from ages 0 to 6 years, is considered the golden age for human growth and development, significantly influencing an individual's future life. Regrettably, instances where children are subjected to maltreatment, particularly violence, hinder their holistic development. Acts of violence adversely impact both the physical and psychological well-being of a child. To address this issue, a digital illustrated book media has been designed to explore the impacts of violence on early childhood and its effects on children's psychological development. This research aims to provide education and awareness regarding the consequences of violence on children to individuals aged 20-35, including both parents and non-parents. The study adopts a descriptive qualitative approach, utilizing the ADDIE model to develop the media. The research findings indicate that the target community can enhance their awareness of child development and minimize adverse psychological effects on children, thereby potentially preventing occurrences of violence from their immediate environment directed towards children.